Primary meningeal osteosarcoma of the brain during childhood - Case report - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 2008)
Primary meningeal osteosarcomas are rare tumors, with only 19 reported cases in the literature; only 4 of these, including the present case, are in pediatric patients. In this report, the authors present the case of an 8-year-old boy with a history of generalized tonic-clonic seizures who was found to harbor a meningeal osteosarcoma within the sylvian fissure. Initial working diagnoses included meningioma and glioma. After tumor enlargement and progressive symptoms, the patient underwent a large frontotemporal craniotomy and complete resection of the lesion, which recurred 6 and 12 months after the initial surgery and was surgically treated after each recurrence. The rarity of primary meningeal osteosarcomas can make their diagnosis difficult, and histopathological evaluation is mandatory for diagnosis. Because of their fast progression, they must be treated aggressively by means of surgery, chemotherapy, and radiotherapy.
Keywords: brain neoplasm; osteosarcoma; recurrence; PRIMARY OSTEOGENIC-SARCOMA; PRIMARY INTRACEREBRAL OSTEOSARCOMA; INTRACRANIAL OSTEOSARCOMA; RADIATION; TUMOR; SKULL; GLIOBLASTOMA; CEREBRUM; BONE